Demand forecast of a product family on different hierarchies - Ong, Li Fong. (2010)
Demand forecasting is inevitable for companies to adopt in today’s context as it determines the demand for the future, bringing in advantageous benefits to a company. In this study, two ways of forecasting were evaluated, namely, to forecast directly on the component level and the other was to forecast on the module level which would be then converted to the component level. Also, ARIMA and Croston methodologies were being evaluated.